Analisis Pengaruh Rasio Keuangan terhadap Reaksi Pasar pada Perusahaan Bursa Efek Indonesia melalui Pendekatan Partial Least Square - Yusrianti Hanike (At-Tauzi : Jurnal Ekonomi Islam, 2020)
Stock movements are a hot topic, especially with the development of capital markets in the country. Moreover, the Indonesian stock market has become a barometer of trading activities in Indonesia. Financial ratios are one measure in looking at a company's ability to manage its economic capabilities. At the other side, market reaction shows changes in stock prices of securities. Through the Partial Least Square (PLS) approach, the resulting model is able to identify indicators of financial ratios to market reactions. PLS is a quantitative modeling of factors that show the relationship between several dependent and independent factors through its indicators. PLS analysis is a combination of path analysis and regression analysis. In this research, financial ratios include liquidity ratios, activities, profitability and solvency. The analysis includes BEI data in the field of Manufacturing in 2016. Based on the results of the study it can be concluded that through financial ratios that the profitability ratio is able to show that the elements have a relationship to the elements in the market reaction. Indicators that are not good in explaining financial ratios affect the relationship to market reaction.